IMPLEMENTATION OF PROBLEM-BASED LEARNING (PBL) MODELS TO IMPROVE STUDENTS' MATHEMATICAL COMMUNICATION ABILITY - Yus Mochamad Cholily; Muhammad Nabil Hibatullah; Minatun Nadlifah (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Math problem-solving skills among students are still lacking. This is demonstrated by kids' inability to comprehend inquiries, offer proper responses, or convey ideas. Low communication ability can also result from instruction that downplays the importance of students' ability to solve problems. This study aimed to determine whether the increase in the mathematical communication skills of students who received problem-based learning models was better than that of conventional learning. Moreover, to find out how students' attitudes toward problem-based learning models. This research method is quasi-experimental, and the research design is a Nonequivalent control group design. The experimental class gets learning with the problem-based learning model, and the control class with conventional learning. The population of this study was all students of class VII SMPN 2 Kota Mojokerto. The samples used were two classes of five selected by purposive sampling technique. To obtain research data, pretest, posttest, and mathematical communication skills were used using the independent sample t-test. Based on the results of data analysis, 1) improving students' mathematical communication ability using problem-based learning models is better than students using conventional learning; 2) students' attitude towards learning mathematics using the problem-based learning model is positive. Kemampuan siswa untuk memecahkan masalah matematika masih rendah. Hal ini ditandai dengan kurangnya siswa dalam memahami pertanyaan dan memberikan jawaban serta mengutarakan pikiran atau ide secara tepat. Rendahnya kemampuan komunikasi juga disebabkan oleh model pembelajaran yang belum menekankan siswa pada aspek pemecahan masalah.Tujuan penelitian ini adalah untuk mengetahui apakah peningkatan kemampuan komunikasi matematis siswa yang memperoleh model pembelajaran problem based learning lebih baik dari pada siswa yang menggunakan pembelajaran konvensional, dan untuk mengetahui bagaimana sikap siswa terhadap model pembelajaran problem based learning. Metode penelitian ini adalah quasi eksperimen dan desain penelitian adalah Nonequivalent control group design. Kelas eksperimen memperoleh pembelajaran dengan model problem based learning dan kelas kontrol dengan pembelajaran konvesional. Populasi dari penelitian ini adalah seluruh siswa kelas VII SMPN 2 Kota Mojokerto, Adapun sampel yang digunakan sebanyak dua kelas dari lima kelas dipilih dengan Teknik purposive sampling. Untuk mendapatkan data hasil penelitian digunakan pretest, posttest, kemampuan komunikasi matematis menggunakan independent Sample t-Test. Berdasarkan hasil analisis data, 1) peningkatan kemampuan komunikasi matematis siswa yang menggunakan model pembelajaran problem based learning lebih baik dari pada siswa yang menggunakan pembelajaran konvensional; 2) sikap siswa terhadap pembelajaran matematika yang menggunakan model pembelajaran problem based learning adalah positif